Effects of power modulation on behaviours of molten pool and keyhole during laser–arc hybrid welding of pure copper - Jie Ning; Lin-Jie Zhang; Liang-liang Zhang; Jian Long; Xian-qing Yin; Jian-Xun Zhang; Suck-Joo Na (Materials & Design, 2020)
Modulated laser power hybrid welding (M-HW) of 4 mm-thick T2 pure copper was conducted to improve the welding stability. It was observed that the sinusoidal modulation of laser power in hybrid welding can reduce the incidence of weld defects such as spatters and pores, and decrease the transverse shrinkage of the weld seam. An observation of the evolution of the molten pool and keyhole using high-speed CCD photography reveals the main reason behind this to be the increase in the instantaneous maximum power because of power modulation, which increases the keyhole depth and frequency of formation of penetrated keyholes. The formation of a penetrated keyhole facilitates the escape of excess energy from the aperture at the bottom of the keyhole, thereby preventing the instability of the bottom of the keyhole caused by over concentration of energy thereat. This reduces the energy transfer within the surroundings of the molten pool, as well as the transverse shrinkage of the weld seam. The effects of the amplitude and the frequency of the sinuous waveforms of laser power on the frequency of formation of penetrated keyholes were analysed.